Sources of China's Economic Growth, 1952-99 : Incorporating Human Capital Accumulation - Wang, Yan; Yao, Yudong (World Bank, Washington, DC, 2014)
China's performance in economic growth, and poverty reduction has been remarkable. There is an ongoing debate about whether this growth is mainly driven by productivity, or factor accumulation. But few past studies have incorporated information on China's human capital stock, and thus contained an omission bias. The authors construct a measure of China's human capital stock from 1952 to 1999, and, using a simple growth accounting exercise, incorporate it in their analysis of the sources of growth, during the pre-reform (1952-77), and the reform period (1978-99). They find that the accumulation of human capital in China (as measured by the average years of schooling for the population aged 15 to 64) was quite rapid, and contributed significantly to growth, and welfare. After incorporating human capital, they also find that the growth of total factor productivity, still plays a positive, and significant role during the reform period. In contrast, productivity growth was negative in the pre-reform period. The results are robust to changes in labor shares in GDP. The recent declining rate of human capital accumulation is a cause for concern, if China is to sustain its improvements in growth, and welfare in the coming decade. Funding for basic education is unevenly distributed, and insufficient in some poor regions.